Disseminated kaposi's sarcoma in an HIV-positive patient: A rare entity in an Indian patient - Biswanath Behera; Laxmisha Chandrashekar; Devinder Mohan Thappa; Pampa Ch Toi; Kolar Vishwanath Vinod (Indian Journal of Dermatology, 2016)
AIDS-associated disseminated Kaposi sarcoma (KS) is a rare entity, especially in India due to the low prevalence of human herpes virus-8 infections in Indian population. Due to its rapid and progressive nature, early diagnosis and institution of highly active antiretroviral therapy is crucial in AIDS-associated KS, with a view to achieving favorable prognosis. We report a case of disseminated KS in an HIV-1 positive patient, who presented with two months history of multiple violaceous patches and plaques over the trunk, bilateral upper limbs, lower limbs, and hard palate. The patient died of recurrent massive pleural effusion before starting antiretroviral therapy. This case is being reported due to the paucity of KS in the Indian literature, especially the disseminated type and to highlight its rapidly progressive course which can be fatal.